ASSESSMENT OF THE EFFECTIVENESS OF CLINICAL ROTATIONS IN NURSING STUDENT’S CLINICAL COMPETENCE, A CROSS- SECTIONAL STUDY AT JAMSHORO PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Background: Clinical competence is essential for ensuring safe and effective nursing care. Clinical rotations provide nursing students with real-world exposure to healthcare environments, where they can apply theoretical knowledge, practices clinical skills, develop professional confidence. This experimental learning is important in preparing students for the demands of clinical practice.Objective: The primary aim of this study was to assess the efficacy of clinical rotations toward enhancing the clinical competence of nursing students in Jamshoro, Pakistan.Methodology: Descriptive cross-sectional study was conducted among 165 BSN students enrolled in two nursing colleges. Data were collected using structured questionnaire on Likert scale, measuring communication skill, critical thinking skill, decision-making skill, and practical patient care skill of the students. The sampling technique used was non-probability convenience sampling. Data are analyzed using SPSS 26.0 and Microsoft Excel.Results: The outcome indicated that clinical rotations reinforced  clinical  competence  significantly  in  several aspects. Approximately 75.7% of the students indicated increased confidence in communicating with patients and families, and 71.5% used evidence in clinical decision- making. Moreover, 69.7% indicated feeling comfortable co- coordinating care with inter-disciplinary teams. Approximately 65% of the students reported an overall competent level in the core clinical domain.Conclusion: Clinical rotations are effective in developing clinical competence among nursing students. Though they enhance communication, decision-making and care confidence, areas such as documentation skills and ethical decisions require additional educational intervention.